Making Room at the Table: Lutheran Ministry in a Religiously Plural America. Issue 3 (4th September 2017) - Grafton, David D.
Abstract: Religious pluralism is a part of the American experience. This article proposes that Christianity in the United States is not under attack, as some claim, but that such religiosity has been a part of the American experience from the very beginning. Such diversity is now more public and acceptable. This reality requires clergy and lay leaders to develop skills to help their congregations navigate their ongoing multi‐faith relationships within families, at work, school, and within civic organizations. The article argues that Christian faithfulness is not a matter of changing what we believe in response to religious pluralism, but how we articulate our beliefs in such a context. Finally, the author proposes several practical guidelines for developing such pastoral skills through the use of Luther's Catechisms.